RGD-Alginate beads as scaffolds for culturing primary human dermal and pulmonary fibroblasts - M.C. Stahl; K.G. Bergendahl; D. Zaytseva-Zotova; K.R. Rytterager; C.T. Nordgård; J.S. Kjesbu; H. Haslene-Hox; Ø. Halaas; P. Sætrom; A.S. Chahal; B.L. Strand (Carbohydrate Polymers, 2026)

Rock Salt Properties for Gas Storage in Mined Caverns: Part I–Short-Term Deformation and Yield, Long-Term Creep, and Gas Sealing Capacity - J. Sarout; M. Sari; L. Esteban; P. P. Mandal; J. Bourdet; D. Nguyen; J. Strand; E. Frery; L. Imbert; A. Francois; L. Langhi; D. Mallants (Rock Mechanics and Rock Engineering, 2026)
Deep rock salt formations can be drilled and solution-mined into caverns for permanent waste disposal, or temporary energy storage (natural gas/compressed air/hydrogen) to alleviate the intermittency of wind/solar energy. We report here the results of the laboratory appraisal of the key properties of a thick Devonian rock salt formation in the Canning Basin (Western Australia). Two representative but contrasting lithofacies were identified: a clean lithofacies made of nearly pure halite, and a dirty lithofacies comprising anhydrite, and dolomite/quartz inclusions. On each lithofacies, we conducted a mineralogical, microstructural and petrophysical characterisation, and a long-term four-stage triaxial test to simulate the impact of depth and anthropogenic stress perturbations. Strains and ultrasonic P-/S-wave velocities were monitored, and at specific stages of the triaxial test, long-term gas transmissivity and creep tests were conducted for up to 16 and 42 days, respectively. At all the triaxial stresses explored, including the in-situ conditions, the oven-dry clean salt facies exhibits a typical gas permeability of 5.10 –5 mD = 5.10 –20 m 2 , whereas the dirty salt is 100 to 1000 times more permeable to gas. The estimated steady-state creep rates are consistent with the extensive collection of literature data also reported here. The dominant creep mechanism is likely dislocation glide, complemented by frictional sliding where damage might exist. Pressure-solution creep is probably not dominant here, especially within the testing time scale. However, water is likely present in deep salt bodies and around man-made salt caverns, promoting overall creep through pressure-solution, and damage healing, hence reducing gas permeability even further.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Herbivory-Induced Nardus stricta Dominance Enriches Plant Silicon Relative to Phosphorus Enforcing Alternative Ecosystem Stable States in an Alpine Environment - G. N. Furey; G. Austrheim; L. T. Strand; J. Mulder; J. D. M. Speed; V. Martinsen (Ecosystems, 2026)
Herbivory can alter plant stoichiometry generating biogeochemical feedbacks that stabilize or drive transitions between ecosystem states. We report results after 23 years from a grazing experiment in Norway comparing five paired exclosures and grazed plots that were complemented with inclusion of five islands serving as a natural control. We tested the hypothesis that herbivory-driven shifts in plant dominance scale to alter elemental stocks and stoichiometry indicative of decelerated ecosystem biogeochemistry. Domestic sheep, Ovis aries , grazing was associated with dominance of the herbivory-resistant grass, Nardus stricta, rich in silicon (Si), while the ungrazed islands harbored a sheep-preferred grass Avenella flexuosa and forbs such as Solidago virgaurea relatively richer in phosphorus (P). Inside the exclosures, N. stricta had lower abundance than under grazing, but remained dominant at most sites. Its persistence suggests hysteresis on the trajectory to an ungrazed state displayed inside one mainland exclosure and on the islands. N. stricta had a high Si:P ratio, and through its dominance, this stoichiometry scaled to aboveground biomass with a more than doubling of the stock of Si (125%) on the mainland compared to the islands and a 46% increase in the concentration of Si. In contrast, the concentration of P in aboveground biomass on the islands was more than double (122%) the mainland. Herbivory appears to stabilize a high-Si ecosystem state compared to a high-P ungrazed state indicated through the plant Si:P ratio in this alpine ecosystem. This enrichment of silicon relative to phosphorus may cascade throughout the ecosystem with far-reaching implications.

The gut microbiome differs between hygiene-performing and non-hygiene-performing worker honey bees - Y. H. Tola; K. Wagoner; M. K. Strand; O. Rueppell; D. R. Tarpy (Insectes Sociaux, 2025)
Gut microbiomes play a significant role in the health, development, and behavior of numerous species, including honey bees ( Apis mellifera ). Worker honey bees exhibit varying degrees of hygienic behavior, which involves the removal of unhealthy brood to mitigate disease within their colony. However, the potential relationship between hygienic behavior and the honey bee gut microbiome has not been previously investigated. In this study, we compared gut microbiota in honey bees engaged in hygienic behavior (hygiene performers) versus those not exhibiting this behavior (non-hygiene performers) using 16S rRNA gene amplicon sequencing. Proteobacteria, Firmicutes, and Actinobacteria were identified as the predominant phyla. Notably, three bacterial species ( Apilactobacillus kunkeei , Bartonella apis, and Frischella perrara ) were found to be more abundant in hygiene performer bees compared to non-hygiene performer bees. Additionally, hygiene performer bees showed a higher diversity of amplicon sequence variants, with Apibacter mensalis being exclusively present in hygiene performer bees and absent in non-hygiene performer bees. These findings reveal an association between gut microbiota composition and hygienic behavior in honey bees, which may provide a foundation for future research exploring probiotic development and other strategies to enhance honey bee health.

Arthropod diversity in constructed wetlands is affected strongly by shoreline properties but only weakly by grazing - David Åhlén; Jerker Jarsjö; Mats Jonsell; Björn K. Klatt; Lea D. Schneider; John Strand; Peter A. Hambäck (Journal of Biogeography, 2024)
Aim Aquatic‐terrestrial transition zones contain features essential for many species that often benefit wetland biodiversity. Shallow flood‐zone areas and reed beds are indicative of natural wetland habitats; however, how such features affect the native arthropod biodiversity in constructed wetlands is scarcely investigated. We asked how these shoreline features, as well as wetland shoreline properties and grazing management, influence riparian arthropod diversities and habitat specializations. Location Constructed wetlands, Sweden. Taxa Araneae, Coleoptera, Diptera. Methods Taxonomic‐, phylogenetic‐ and trait diversities, along with habitat specialist species richness, were measured in riparian spiders, beetles and selected Diptera in 68 constructed wetlands in two regions of Sweden. We ran structural equation models to estimate direct and indirect effects from shoreline slope, flooded grassland, reed areas and grazing management on group diversities, and used multivariate models to determine drivers on habitat specialist species richness. Results Flooded grassland and reed area, along with shoreline slope influenced arthropod diversities, and responses differed between arthropod groups and diversity metrics. Spider trait diversity was greater in wetlands with larger flooded grassland areas, whilst beetle trait diversity was reduced. Spider phylogenetic diversity was greater in wetlands containing larger reed areas and in wetlands with steeper shorelines. However, species richness in predatory flies was greater in wetlands with more gentle shorelines. Grazing management had limited effects on arthropod diversities; however, species richness in wetland specialist and generalist predatory dipterans was greater in the absence of grazers in wetlands with greater flooded grassland areas. Main Conclusions As requirements vary considerably among arthropods, care must be taken when constructing and managing wetlands to benefit arthropod biodiversity. The present results suggest wetlands with a varied shoreline, albeit with greater proportions of flood areas, or multiple adjacent wetlands with varying shores in a wet landscape and a mild grazing regiment, would accommodate a more diverse arthropod fauna.

P25-12 Effects of personalized chemical mixture on endocrine disruption based on estrogen nuclear receptors - L. Reis; D. Strand; B. Lundgren; J. Martin; O. Karlsson (Toxicology Letters, 2024)

P25-13 Effects of personalized mixtures of POPs on steroidogenesis and viability in H295R cells - D. Strand; B. Lundgren; J.W. Martin; O. Karlsson (Toxicology Letters, 2024)

Evaluating the contribution of plant metabolic pathways in the light to the ATP:NADPH demand using a meta-analysis of isotopically non-stationary metabolic flux analyses - Kaila Smith; Deserah D. Strand; Berkley J. Walker (Photosynthesis Research, 2024)
Balancing the ATP: NADPH demand from plant metabolism with supply from photosynthesis is essential for preventing photodamage and operating efficiently, so understanding its drivers is important for integrating metabolism with the light reactions of photosynthesis and for bioengineering efforts that may radically change this demand. It is often assumed that the C3 cycle and photorespiration consume the largest amount of ATP and reductant in illuminated leaves and as a result mostly determine the ATP: NADPH demand. However, the quantitative extent to which other energy consuming metabolic processes contribute in large ways to overall ATP: NADPH demand remains unknown. Here, we used the metabolic flux networks of numerous recently published isotopically non-stationary metabolic flux analyses (INST-MFA) to evaluate flux through the C3 cycle, photorespiration, the oxidative pentose phosphate pathway, the tricarboxylic acid cycle, and starch/sucrose synthesis and characterize broad trends in the demand of energy across different pathways and compartments as well as in the overall ATP:NADPH demand. These data sets include a variety of species including Arabidopsis thaliana , Nicotiana tabacum , and Camelina sativa as well as varying environmental factors including high/low light, day length, and photorespiratory levels. Examining these datasets in aggregate reveals that ultimately the bulk of the energy flux occurred in the C3 cycle and photorespiration, however, the energy demand from these pathways did not determine the ATP: NADPH demand alone. Instead, a notable contribution was revealed from starch and sucrose synthesis which might counterbalance photorespiratory demand and result in fewer adjustments in mechanisms which balance the ATP deficit.

Tracking rapid ice recession in a major Southern Alps valley during the last glacial termination - Peter D. Strand; Aaron E. Putnam; Joerg M. Schaefer; George H. Denton; David J.A. Barrell (Quaternary Science Reviews, 2024)

Integrative demographic modelling reduces uncertainty in estimated rates of species' historical range shifts - Antonio R. Castilla; Alissa Brown; Sean Hoban; Everett Andrew Abhainn; John D. Robinson; Jeanne Romero‐Severson; Adam B. Smith; Allan E. Strand; John R. Tipton; Andria Dawson (Journal of Biogeography, 2024)
Aim Biogeographers have used three primary data types to examine shifts in tree ranges in response to past climate change: fossil pollen, genetic data and contemporary occurrences. Although recent efforts have explored formal integration of these types of data, we have limited understanding of how integration affects estimates of range shift rates and their uncertainty. We compared estimates of biotic velocity (i.e. rate of species' range shifts) using each data type independently to estimates obtained using integrated models. Location Eastern North America. Taxon Fraxinus pennsylvanica Marshall (green ash). Methods Using fossil pollen, genomic data and modern occurrence data, we estimated biotic velocities directly from 24 species distribution models (SDMs) and 200 pollen surfaces created with a novel Bayesian spatio‐temporal model. We compared biotic velocity from these analyses to estimates based on coupled demographic‐coalescent simulations and Approximate Bayesian Computation that combined fossil pollen and SDMs with population genomic data collected across the F. pennsylvanica range. Results Patterns and magnitude of biotic velocity over time varied by the method used to estimate past range dynamics. Estimates based on fossil pollen yielded the highest rates of range movement. Overall, integrating genetic data with other data types in our simulation‐based framework reduced apparent uncertainty in biotic velocity estimates and resulted in greater similarity in estimates between SDM‐ and pollen‐integrated analyses. Main Conclusions By reducing uncertainty in our assessments of range shifts, integration of data types improves our understanding of the past distribution of species. Based on these results, we propose further steps to reach the integration of these three lines of biogeographical evidence into a unified analytical framework.

Beach litter sources around Nuuk, Greenland: An analysis by UArctic summer school graduate course students - Marthe Larsen Haarr; Lis Bach; Catherine P. Chambers; Jannike Falk-Andersson; Thomas Juul-Pedersen; Ryan d'Arcy Metcalfe; Anna Sinisalo; Jakob Strand; Helene Svendsen; Julia E. Baak; Helga Hvanndal Björnsdóttir; Elsa Margaret Krook Brenner; et al. (Marine Pollution Bulletin, 2023)

Tradeoffs and synergies in wetland multifunctionality: A scaling issue - P.A. Hambäck; L. Dawson; P. Geranmayeh; J. Jarsjö; I. Kačergytė; M. Peacock; D. Collentine; G. Destouni; M. Futter; G. Hugelius; S. Hedman; S. Jonsson; et al. (Science of The Total Environment, 2023)

Hypoxia constrains behavioral responses to chemical alarm cues by fathead minnows Pimephales promelas - Madisen C. Strand; Isabel G. DeVriendt; Alex R. Seigel; Christopher L. Merkord; Brian D. Wisenden (Environmental Biology of Fishes, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Association of predation risk with a heterospecific vocalization by an anabantoid fish - Alex R. Seigel; Isabel G. DeVriendt; Madisen C. Strand; Ananda Shastri; Brian D. Wisenden (Journal of Fish Biology, 2022)
Honey gouramis ( Trichogaster chuna ) received chemical alarm cues derived from conspecific epidermal tissue and, simultaneously, the vocalization produced by a heterospecific gourami species, the sparkling pygmy gourami ( Trichopsis pumila ). Control trials paired water with the vocalization. In trials that received alarm cues, honey gouramis significantly increased activity relative to control trials that received water, suggesting an attempt to flee and search for refuge. When the recording of the vocalization was later replayed to test fish without any additional chemical cue, fish that had previously experienced the alarm cue froze while those that had received water with the vocalization did not change their behaviour. These data indicate that honey gouramis recognize and respond to chemical alarm cues, making this report the second anabantoid species to be recorded with this response. Second, these data indicate that honey gouramis can associate risk of predation with a novel auditory stimulus, including vocalizations from other species. These data suggest the potential for vocalizations to evolve into alarm signals in this group of fishes.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

Regulation of chloroplast primary metabolism - Ute Armbruster; Deserah D. Strand (Photosynthesis Research, 2020)

Light-Weight Portable Electroantennography Device as a Future Field-Based Tool for Applied Chemical Ecology - Stephen M. Pawson; Jessica L. Kerr; Brooke C. O’Connor; Philippe Lucas; Dominique Martinez; Jeremy D. Allison; Tara M. Strand (Journal of Chemical Ecology, 2020)

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Forecasting the genetic influences of red drum stock enhancement in South Carolina - Christopher J. Katalinas; John D. Robinson; Allan E. Strand; Tanya Darden; Karl Brenkert; Michael R. Denson (Fisheries Management and Ecology, 2019)
The South Carolina Department of Natural Resources ( SCDNR ) began stocking red drum, Sciaenops ocellatus (Linnaeus), in 1989 to augment the abundance of juveniles available for recreational harvest in South Carolina estuaries. While stock enhancement can help supplement wild populations under high fishing pressure, releasing hatchery‐raised fish into the wild also presents the risk of decreased genetic diversity. An individual‐based model ( IBM ) was developed to forecast the genetic influences of stocking on the wild spawning population to inform responsible stocking strategies. Model results indicated the SCDNR red drum stock enhancement programme should maintain mean contributions of stocked fish no greater than 30% per year class over a 45‐year stocking period, coupled with at least 10 effective breeders in the hatchery replaced annually, to maintain current levels of genetic diversity estimated in the wild population. The IBM is a useful tool for hatchery managers to guide responsible stock enhancement.

Ice-confined construction of a large basaltic volcano—Austurfjöll massif, Askja, Iceland - A. H. Graettinger; D. W. McGarvie; I. P. Skilling; A. H. Höskuldsson; K. Strand (Bulletin of Volcanology, 2019)

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Agricultural land usage transforms nitrifier population ecology - Anthony D. Bertagnolli; Dylan McCalmont; Kelley A. Meinhardt; Steven C. Fransen; Stuart Strand; Sally Brown; David A. Stahl (Environmental Microbiology, 2016)
Summary Application of nitrogen fertilizer has altered terrestrial ecosystems. Ammonia is nitrified by ammonia and nitrite‐oxidizing microorganisms, converting ammonia to highly mobile nitrate, contributing to the loss of nitrogen, soil nutrients and production of detrimental nitrogen oxides. Mitigating these costs is of critical importance to a growing bioenergy industry. To resolve the impact of management on nitrifying populations, amplicon sequencing of markers associated with ammonia and nitrite‐oxidizing taxa (ammonia monooxygenase‐ amo A , nitrite oxidoreductase‐ nxr B , respectively) was conducted from long‐term managed and nearby native soils in Eastern Washington, USA . Native nitrifier population structure was altered profoundly by management. The native ammonia‐oxidizing archaeal community (comprised primarily by N itrososphaera sister subclusters 1.1 and 2) was displaced by populations of N itrosopumilus , N itrosotalea and different assemblages of N itrososphaera (subcluster 1.1, and unassociated lineages of N itrososphaera ). A displacement of ammonia‐oxidizing bacterial taxa was associated with management, with native groups of Nitrosospira (cluster 2 related, cluster 3A.2) displaced by N itrosospira clusters 8B and 3A.1. A shift in nitrite‐oxidizing bacteria ( NOB ) was correlated with management, but distribution patterns could not be linked exclusively to management. Dominant nxrB sequences displayed only distant relationships to other NOB isolates and environmental clones.

Genetic structure along the strandline: Unravelling invasion history in a one‐dimensional system - Sara Ohadi; Peter K. Ades; Rebecca Ford; Allan E. Strand; Josquin Tibbits; Mohsen B. Mesgaran; Roger D. Cousens (Journal of Biogeography, 2016)
Aim To unravel the genetic processes involved in a case of invasion by one species, the self‐incompatible Cakile maritima Scop. (Brassicaceae) in Australia, as it has replaced a related prior invader, Cakile edentula (Bigelow) Hook. Location Southern and eastern coastlines of Australia. Methods Genetic diversity within and between populations was characterized at a continental scale using microsatellite ( SSR ) markers to examine nuclear diversity and cleaved amplified polymorphic sequence ( CAPS ) markers to examine chloroplasts. DNA was sourced from 24 populations of C. maritima along its putative invasion trajectory and, for comparison, from four populations of C. edentula that are currently being invaded by C. maritima . Analysis of Molecular Variance and a Bayesian assignment method were used to explore the data. Results No evidence was found for progressive loss of diversity in C. maritima in the putative direction of range expansion. Western and south‐eastern populations of C. maritima have almost certainly resulted from independent introductions, although there is evidence of very limited gene flow from west to east. There was considerably greater, spatially structured variation in the south‐east, suggesting multiple introductions of C. maritima to that region. We found evidence of hybridization and introgression from C. edentula into C. maritima , both in the two regions where they are currently sympatric and elsewhere. Main conclusions The invasion history of a species spreading in a largely one‐dimensional habitat can still be highly complex and difficult to interpret. Regional patterns of variation in C. maritima indicate several introductions from different parts of the native range, limited gene flow from the first introduction eastwards and genetic drift within Western Australia. There has also been bi‐directional gene flow between this species and C. edentula . The significance of the introgression from C. edentula into C. maritima with respect to natural selection, however, remains to be determined.

Population structure in a critically endangered arctic fox population: does genetics matter? - L. DALÉN; K. KVALØY; J. D. C. LINNELL; B. ELMHAGEN; O. STRAND; M. TANNERFELDT; H. HENTTONEN; E. FUGLEI; A. LANDA; A. ANGERBJÖRN (Molecular Ecology, 2006)
The arctic fox ( Alopex lagopus ) in Scandinavia is classified as critically endangered after having gone through a severe decline in population size in the beginning of the 20th century, from which it has failed to recover despite more than 65 years of protection. Arctic foxes have a high dispersal rate and often disperse over long distances, suggesting that there was probably little population differentiation within Scandinavia prior to the bottleneck. It is, however, possible that the recent decline in population size has led to a decrease in dispersal and an increase in population fragmentation. To examine this, we used 10 microsatellite loci to analyse genetic variation in 150 arctic foxes from Scandinavia and Russia. The results showed that the arctic fox in Scandinavia presently is subdivided into four populations, and that the Kola Peninsula and northwest Russia together form a large fifth population. Current dispersal between the populations seemed to be very low, but genetic variation within them was relatively high. This and the relative F ST values among the populations are consistent with a model of recent fragmentation within Scandinavia. Since the amount of genetic variation is high within the populations, but the populations are small and isolated, demographic stochasticity seems to pose a higher threat to the populations’ persistence than inbreeding depression and low genetic variation.

Estimating the patch size of larval fishes during colonization on coral reefs - D. Lecchini; V. Dufour; J. Carleton; S. Strand; R. Galzin (Journal of Fish Biology, 2004)
Fish larvae were sampled daily over a period of 14 days using six crest nets spaced at 200 m intervals on a coral reef on the west coast of Moorea Island, French Polynesia, to estimate the extent to which ichthyonekton arriving at one location reflected ichthyonekton arriving at neighbouring areas. Each night, the six crest nets were colonized by larval fishes from the same location.

Integrating biodiversity priorities with conflicting socio-economic values in the Guinean–Congolian forest region - P.H. Williams; J.L. Moore; A. Kamden Toham; T.M. Brooks; H. Strand; J. D'Amico; M. Wisz; N.D. Burgess; A. Balmford; C. Rahbek (Biodiversity and Conservation, 2003)